Enhanced ODR Reflection by Using Sio2 Exponentially Graded Materials for 1D Photonic Crystals - Vimal, Sanjeev Sharma (International Journal of Advanced Science and Technology, 2019)
An exponentially graded index material for one dimensional structure of binary & ternary photonic crystal has been proposed. It works as a perfect mirror at third transmission window (1550 nm).A transfer matrix method has been used to estimate the reflection properties of semiconductor materials. An enhanced ODR range is obtained by using both binary and ternary photonic crystal in which Ge as exponentially graded material. In the proposed structure when a third semiconductor layer (GaAs) is introduced between SiO2 and Ge semiconductor photonic crystals the ODR range is increased. This property shows that one dimensional graded index ternary photonic crystal structures have widened ODR than Binary photonic crystals. Therefore broadband omnidirectional photonic bandgap is applicable for many prospects such as omnidirectional mirrors, optical switches, ﬁlters, WDM etc. for optical fiber communications. Keywords: Exponentially graded material, refractive index, optical mirror.